Enhanced maintenance of genetic integrity in induced pluripotent stem cells - Chen, I-Chung (ProQuest Dissertations & Theses, 2014)
During the past eight years, the field of induced pluripotent stem cells (iPSCs) has thrived due to the great practical potential of these cells for use in regenerative medicine. Unlike embryonic stem cells, the requirement for use of embryos does not apply to iPSC derivation, and patient-specific iPSCs can be derived directly from each patient, which eliminates ethical concerns as well as the issue of immune rejection, respectively. However, a remaining safety concern is that iPSCs are derived from somatic cells that typically bear a greater mutation load than germ cells or pluripotent cells. Additionally, it has been shown that the reprogramming efficiency of somatic cells to form iPSCs is increased by repression of p53. Thus, that raises another safety issue with respect to the use of iPSCs in clinical applications, because p53 functions as the 'guardian of the genome' and reducing or eliminating its function could negatively impact genetic integrity. Therefore, the genetic integrity of iPSCs and their differentiated derivatives needs to be carefully investigated before implementing iPSCs for clinical use. The focus of this dissertation has been to test our central hypothesis that enhanced genetic integrity is maintained in pluripotent stem cells. Here, we used Big Blue transgenic mice harboring the lacI mutation-reporter transgene to demonstrate that the spontaneous mutation frequency was initially high in starting differentiated tail tip fibroblasts (TTFs), but was then much lower in iPSCs derived from these fibroblasts, and then rose again in fibroblasts differentiated from the iPSCs to levels as high or higher than those in the starting TTFs. Surprisingly, the mutation frequency was no different in p53 mutant iPSCs and wild type iPSCs, suggesting that a transient knockdown of p53 in cells that are already pluripotent might not affect the genetic integrity of iPSCs. However, the mutation frequency was two-fold higher in p53 mutant fibroblasts differentiated in vitro relative to wild type fibroblasts differentiated in vitro. These results suggest that enhanced maintenance of genetic integrity is a fundamental characteristic of pluripotent cells, and that the mechanisms responsible for enhanced genetic integrity are subject to reprogramming during the derivation or subsequent directed differentiation of iPSCs. These results also provide insight into the safety of cells derived from iPSCs for potential therapeutic applications.